Skogs- och energibolagens attityd till förnybara drivmedel vid upphandling av transporttjänster i norra Sverige - Johansson, Greger; Regemar, Daniel (2013)
Sweden's government is dedicated to the goal of having a vehicle fleet that is independent of fossil fuels by 2030. Achieving these goals requires, among other things, new types of fuel that give lower net emissions of carbon dioxide. The present market includes stations offering lowlevel blends of renewable fuels in conventional diesel as well as some stations offering renewable fuels only. The purpose of this study is to survey purchasers’ attitudes to the use renewable fuels in roundwood and bioenergy transport in forest- and energy companies. The study was based on qualitative interviews through a combination of face-to-face meetings and telephone interviews with each sample group. The total number of respondents was ten (10), consisting of five (5) from forest companies and five (5) from energy companies. Transport service purchasers were generally positive to renewable fuels and considered these necessary in the future. At present they see a lack of adequate technology and availability for wider use. Energy companies felt they had a lower level of insight into the use of renewable fuels. This may be due to the fact that many bioenergy delivery agreements specify the transport service as the responsibility of the supplier. Both sample groups said that it is primarily the market, i.e. end users who must be prepared to pay for the extra cost to use more environmentally friendly and renewable fuels. Sveriges regering har som ambition att vid år 2030 skall Sverige ha en fordonsflotta som är oberoende av fossila drivmedel. För att nå målen krävs bl.a. nya typer av drivmedel på marknaden som ger ett lägre nettoutsläpp av fossilt koldioxid. Det finns på marknaden idag både låginblandning av förnybara drivmedel i vanlig diesel och stationer med enbart förnyelsebart drivmedel. Syftet med denna studie är att kartlägga attityden till förnybara drivmedel hos upphandlare av transporter inom skogs- och energibolag då båda dessa branscher är stora uppköpare av transporter av skogsråvara. Studien genomfördes med hjälp av ...